How we manage Gaucher Disease in the era of choices. (29th May 2018) - Revel‐Vilk, Shoshana; Szer, Jeff; Mehta, Atul; Zimran, Ari
Summary: Treatment of Gaucher Disease (GD) is now beset with the abundance of therapeutic options for an individual patient, making the choice of therapy complex for both expert and non‐expert clinicians. The pathogenesis of all disease manifestations is a gene mutation‐driven deficiency of glucocerebrosidase, but the clinical expression and response of each of the clinical manifestations to different therapies can be difficult to predict. Enzyme replacement therapy has been available since 1991 and is well‐established, with known efficacy and minimal toxicity. Of interest, the three available enzymes are distinct molecules and were registered as new products, not biosimilars. Oral substrate reduction therapy has undergone a revitalisation with a newly approved agent in this class for which some efficacy and toxicity questions have been raised. Herein we present our approach to the management of GD in the era of choices, including a new algorithm for how to manage a newly diagnosed patient.